2020
DOI: 10.1002/adfm.202002528
|View full text |Cite
|
Sign up to set email alerts
|

Positioning MXenes in the Photocatalysis Landscape: Competitiveness, Challenges, and Future Perspectives

Abstract: MXenes are becoming a worthy contender for boosting the efficacy of semiconductor photocatalysts because of their rich surface and electronic properties, which is exemplified to be a dynamic yet open‐ended exploration of the materials space. Herein, the promise that MXenes hold for photocatalytic applications is elucidated by presenting the various roles of MXenes in the preparation of composite photocatalysts and enhancing their activity and stability. A specific focus is put on the key issues that should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(76 citation statements)
references
References 224 publications
(533 reference statements)
0
76
0
Order By: Relevance
“…Recently, significant progress in the conversion of 2D MXene-based photocatalysts into solar fuels, reasonable design and specific effects of MXene photocatalysts for the production of photocatalytic solar fuels have been reported [ 82 ]. For example, Xie et al [ 83 ] introduced various roles of MXene in preparing composite photocatalysts and improving their activity and stability, clarified their application prospects in photocatalysis, and provided beneficial basis for the rational design and synthesis of efficient and stable MXene-based photocatalysts. It was found that the performance of the layered nanostructure MXene in environmental and energy photocatalysis is amazing, especially those composite materials hybridized with MXene fully demonstrating the excellent characteristics of this special structure [ 83 ].…”
Section: Applications Of the MC Mxene-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, significant progress in the conversion of 2D MXene-based photocatalysts into solar fuels, reasonable design and specific effects of MXene photocatalysts for the production of photocatalytic solar fuels have been reported [ 82 ]. For example, Xie et al [ 83 ] introduced various roles of MXene in preparing composite photocatalysts and improving their activity and stability, clarified their application prospects in photocatalysis, and provided beneficial basis for the rational design and synthesis of efficient and stable MXene-based photocatalysts. It was found that the performance of the layered nanostructure MXene in environmental and energy photocatalysis is amazing, especially those composite materials hybridized with MXene fully demonstrating the excellent characteristics of this special structure [ 83 ].…”
Section: Applications Of the MC Mxene-based Nanomaterialsmentioning
confidence: 99%
“…For example, Xie et al [ 83 ] introduced various roles of MXene in preparing composite photocatalysts and improving their activity and stability, clarified their application prospects in photocatalysis, and provided beneficial basis for the rational design and synthesis of efficient and stable MXene-based photocatalysts. It was found that the performance of the layered nanostructure MXene in environmental and energy photocatalysis is amazing, especially those composite materials hybridized with MXene fully demonstrating the excellent characteristics of this special structure [ 83 ]. At present, MXene composite materials have been applied to the research of dye-sensitized photocatalysis.…”
Section: Applications Of the MC Mxene-based Nanomaterialsmentioning
confidence: 99%
“…The transformation of 2D layered MXenes into 3D macroscopic hydrogel has recently shown tremendous photocatalysis potential [ 70 , 71 ]. When MXenes are assembled into hydrogel systems, they offer exciting and versatile platforms to design MXene-based soft materials with tunable properties [ 72 ].…”
Section: Mxenes In Chemical Adsorption Of Pollutantsmentioning
confidence: 99%
“…30,31 MXenes represent 2D metal carbides, nitrides, and carbonitrides with the formula of M n+1 X n T x , where n ¼ 1, 2, 3, and 4, M represents transition metals, X corresponds to carbon and/or nitrogen, and T x stands for terminal groups. [32][33][34][35] The large surface area, rich surface groups, and opportune stability towards redox surroundings make 2D MXenes competent for assembling nanometals to achieve reinforced aqueous catalytic activity. [36][37][38][39] Hitherto, the anchoring of Bi nanoparticles on MXenes for catalyzing NaBH 4 to hydrogenate nitroarenes remains to be explored.…”
Section: Introductionmentioning
confidence: 99%